Rancang Bangun Sistem Informasi Seleksi Penerimaan Mahasiswa Baru Berbasis Web Menggunakan Metode Agile - Muhammad Yunus Rangkuti; Amanda Fitri Nuraini; Ari Awaludin; Kevin Ferdiansyah (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
The The New Student Admission Selection (SPMB) process requires a system capable of managing registration data in a structured and easily accessible manner. Manual data management has the potential to cause problems such as recording errors, process delays, and difficulties in managing applicant information. Therefore, the design and development of a web-based SPMB information system using the Agile method was conducted. The Agile method was applied to support an iterative and incremental development process, allowing system requirements to be adjusted according to user needs during development. The system provides features for online prospective student registration, applicant data management by administrators, and the delivery of selection result information. The results indicate that the developed system functions properly and supports more effective and organized management of new student admission data.